The impact of the digital revolution on human brain and behavior: where do we stand? . Issue 2 (30th June 2020) - Korte, Martin
Abstract : This overview will outline the current results of neuroscience research on the possible effects of digital media use on the human brain, cognition, and behavior. This is of importance due to the significant amount of time that individuals spend using digital media. Despite several positive aspects of digital media, which include the capability to effortlessly communicate with peers, even over a long distance, and their being used as training tools for students and the elderly, detrimental effects on our brains and minds have also been suggested. Neurological consequences have been observed related to internet/gaming addiction, language development, and processing of emotional signals. However, given that much of the neuroscientific research conducted up to now relies solely on self-reported parameters to assess social media usage, it is argued that neuroscientists need to include datasets with higher precision in terms of what is done on screens, for how long, and at what age.